Applications of RNA-Seq and Omics Strategies From Microorganisms to Human Health - Marchi, Fabio A.; Cirillo, Priscila D.R; Mateo, Elvis C. (IntechOpen, 2017)
The large potential of RNA sequencing and other "omics" techniques has contributed to the production of a huge amount of data pursuing to answer many different questions that surround the science's great unknowns. This book presents an overview about powerful and cost-efficient methods for a comprehensive analysis of RNA-Seq data, introducing and revising advanced concepts in data analysis using the most current algorithms. A holistic view about the entire context where transcriptome is inserted is also discussed here encompassing biological areas with remarkable technological advances in the study of systems biology, from microorganisms to precision medicine.